Clinical validation of a single-tube PCR and reverse dot blot assay for detection of common α-thalassaemia and β-thalassaemia in Chinese. Issue 2 (February 2022) - Liang, Hong-Feng; Li, Lie-Jun; Yang, Hui; Zheng, Xiang-Bin; Lu, Min; Ge, Yi-Yuan; Lin, Fen; Xie, Long-Xu; Yang, Li-Ye
Objective: To evaluate a novel reverse dot blot assay for the simultaneous detection six types of common α-thalassaemia alleles (three deletional and three common non-deletional mutations) and 19 types of common β-thalassaemia alleles in a Chinese population. Methods: Genomic DNA samples were collected from three hospitals in southern China. The novel thalassaemia gene assay involved one multiplex polymerase chain reaction amplification system and one round of hybridization. Each of the clinically validated DNA samples was re-tested using the new multiplex polymerase chain reaction/reverse dot blot assay II (M-PCR/RDB II) assay in a double-blind manner. Results: A total of 1060 unrelated study participants, including 829 patients with thalassaemia and 231 healthy control subjects, were analysed. The whole PCR and RDB procedures were completed in 260 min. All the samples, including heterozygous thalassaemia, homozygous thalassaemia and compound heterozygous thalassaemia, were correctly genotyped, yielding 100% concordance with the reference assays. HKαα/– SEA and HKαα/−α 4.2, which were not included in the detection panel, yielded a contradictory result with this new assay. Conclusion: The novel M-PCR/RDB II assay was simple, rapid and accurate, suggesting that it could be used for the genetic screening and clinical diagnosis of common α-thalassaemia and β-thalassaemia variants in Chinese populations.